Effect of Cadmium Doping on the Optical Properties of As2(S, Se)3 Chalcogenide Thin Films - Grytsyshche, I.V.; Kozak, M.I.; Turok, I.I.; Solomon, A.M.; Loya, V.Yu. (Physics and Chemistry of Solid State, 2015)
As2S3 and As2Se3 chalcogenide glasses doped with cadmium were synthesized in quartz ampoules. Thin chalcogenide films based on the synthesized compounds were deposited by thermal vacuum evaporation. Optical transmission spectra of the obtained films were measured and refractive index values were determined. For the films under investigation the energy bandgap, effective dispersion oscillator energy, and dispersion energy values were determined. Based on the material dispersion parameters, ionicity degree was estimated.